(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To summarize the role of the traditional “kidney-tonifying and yang-warming/kidney-tonifying and essence-benefiting” mechanism in male reproduction; to synthesize representative clinical and experimental evidence on related interventions for male infertility and/or semen abnormalities; and to analyze biological bridging mechanisms involving the hypothalamic–pituitary–testicular (HPT) axis, spermatogenesis, and sperm quality. Methods: A structured narrative review with a system-oriented search was conducted in PubMed/MEDLINE and Web of Science up to October 2025, supplemented by manual reference screening. A PICO/PECO framework was applied, prioritizing RCTs, systematic reviews/meta-analyses, and mechanistic studies with clearly defined interventions; case reports/expert opinions and studies with insufficient data were excluded. Results: Evidence was organized into four intervention categories: (i) kidney-tonifying multi-herb formulas; (ii) representative compounds/herbal units (e.g., icariin), with predominantly preclinical evidence; (iii) combinations of vitamins or L-carnitine with traditional interventions showing more consistent quantitative signals—most notably L-carnitine plus traditional medicine reporting a higher pregnancy rate (RR 1.65) and improvements in multiple semen parameters and testosterone; and (iv) acupuncture, with heterogeneous outcomes. Major gaps included limited hard endpoints (live birth), substantial intervention/outcome heterogeneity, and variable methodological quality. Conclusion: Kidney-tonifying and yang-warming/essence-benefiting approaches may serve as selective adjunctive options for male infertility, but confidence depends on intervention type and evidence quality; high-quality standardized RCTs with long-term safety monitoring and hard reproductive outcomes are needed.